PROGRAM JUMANTIK CILIK TANGGAP BOCAH DALAM PEMBERANTASAN SARANG NYAMUK DI PUSKESMAS SLEMAN, KABUPATEN SLEMAN - Rusita Nurwidi Astuti; Hari Kusnanto; Retna Siwi Padmawati (Journal of Health Service Management, 2016)
Background: Dengue fever (DHF) is an endemic disease inSleman District. Number of dengue cases up to December 2014recorded 538 cases (IR 50,6/100,000 population) with the deathof 4 people (CFR 0,7%). One village in the region of SlemanPrimary Health Care (PHC) always have dengue casesannually are Caturharjo village. On that basis Sleman PHCforming and pioneering activities childrens larva observernamed Tanggap Bocah (TABO) consisting of primary schooland secondary school children with built hamlets first isGanjuran Hamlet, Village Caturharjo and became active in2012. TABO itself is expected to encourage communityparticipation in dengue mosquito nest eradication, reduce DHFmorbidity and improve ABJ in Village Caturharjo. Objective: The objective of this research is to get an overview ofmonitoring the implementation of the TABO in Sleman PHC.Methods: This study is a qualitative research with case studydesign. Results: Implementation of PJB by Jumantik TABO onPSN DBD as a form of community participation among childrenin the prevention of dengue disease with the primary goal ofplanting clean and healthy behavior (PHBS) early. Although nospecial training is given in addition to coaching and monitoring,Jumantik TABO willing and able as extension for friends,families and society as individuals. The increase in denguecases and decrease in ABJ indicate a change in behavior andcommunity participation in PSN as a result of activities JumantikTABO. Conclusions: Implementation TABO in the prevention ofdengue fever in the village Caturharjo running effectively andaccording to expectations with the declining number of DHFcases and increasing ABJ and behavioral changes in thecommunity in PSN DBD and PHBS.